2017
DOI: 10.1136/gutjnl-2017-313832
|View full text |Cite
|
Sign up to set email alerts
|

Favouring modulation of circulating lipoproteins and lipid loading capacity by direct antiviral agents grazoprevir/elbasvir or ledipasvir/sofosbuvir treatment against chronic HCV infection

Abstract: The DAA treatment of patients with chronic hepatitis C might lead to efficient HCV eradication and hepatic improvement concomitantly evolving with favouring lipoprotein/apo metabolisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 50 publications
(36 reference statements)
4
33
0
1
Order By: Relevance
“…In the era of DAA, increased levels of Chol and LDL‐C follow the clearance of HCV has been reported. Our study investigating the dynamic changes of the loading capacities of VLDL and LDL‐C following DAA treatment revealed that the TG and Chol loading capacities in VLDL and the Chol loading capacity in LDL‐C rapidly increased following SVR . These results indicated that large amounts of lipids released from the liver into blood circulation may increase levels of Chol and LDL‐C, resulting in the hydrolysis of TG.…”
Section: Chronic Hepatitis Viral Infection and Lipid Profilesmentioning
confidence: 73%
See 3 more Smart Citations
“…In the era of DAA, increased levels of Chol and LDL‐C follow the clearance of HCV has been reported. Our study investigating the dynamic changes of the loading capacities of VLDL and LDL‐C following DAA treatment revealed that the TG and Chol loading capacities in VLDL and the Chol loading capacity in LDL‐C rapidly increased following SVR . These results indicated that large amounts of lipids released from the liver into blood circulation may increase levels of Chol and LDL‐C, resulting in the hydrolysis of TG.…”
Section: Chronic Hepatitis Viral Infection and Lipid Profilesmentioning
confidence: 73%
“…Our study investigating the dynamic changes of the loading capacities of VLDL and LDL-C following DAA treatment revealed that the TG and Chol loading capacities in VLDL and the Chol loading capacity in LDL-C rapidly increased following SVR. 129 These results indicated that large amounts of lipids released from the liver into blood circulation may increase levels of Chol and LDL-C, resulting in the hydrolysis of TG. However, studies on the long-term dynamics of lipid profile following SVR and the effects on clinical outcomes, especially cardiovascular events, must be conducted afterwards.…”
Section: Chroni C Hepatitis Vir Al Infec Ti On and Lipid Profile Smentioning
confidence: 83%
See 2 more Smart Citations
“…And patients with diabetes were noted to have an elevation in cholesterol after treatment (P=0.05 by Wilcoxon test; n=10), but no significant change in triglycerides (P=0.50 by Wilcoxon test; n=7) [48].In line with these results, several clinical studies provided strong evidence that lipoprotein levels and liver lipid accumulation were inclined to normalize after the initiation of combination therapy including sofosbuvir/ribavirin, sofosbuvir/ledipasvir, asunaprevir/daclatasvir and grazoprevir/elbasvir. These modifications appear to be associated with significant improvement of steatosis and atherogenesis [49][50][51][52][53].…”
Section: Recovery Of Metabolic Damagementioning
confidence: 99%